Evaluation of various steel types for the evolution of hydrogen in KOH - Julke, Falk Michel (2014)
This paper studies the electrochemical behaviour of different types of low-cost commercial steel (A36, 430 and 304) as electrodes to obtain hydrogen. The aim of this work was to understand hydrogen evolution. The studies were conducted by different electrochemistry techniques like chronoamperometry and voltamperometric curves in different concentrations of KOH (5% and 25% m/m). The 304 stainless steel type in a 25% m/m KOH concentration had the best performance, because in these conditions the potential onset of hydrogen release decreased, demonstrating the lowest potential requirement for use as a bipolar plate.